Individual-Level Determinants of Self-Care Behaviors and Adaptation to Chronic Illness in Turkish Patients With Chronic Disease: A Single-Center Cross-Sectional Study - Kılıç YF; Yardımcı Gürel T (Journal of Multidisciplinary Healthcare)
Yasin Furkan Kılıç,1 Tuğba Yardımcı Gürel2 1Coronary Intensive Care Unit, Samsun Training and Research Hospital, Samsun, Turkey; 2Department of Nursing, Sinop University, Sinop, TurkeyCorrespondence: Tuğba Yardımcı Gürel, Department of Nursing, Sinop University, Faculty of Health Sciences, Sinop, 57100, Turkey, Email yardimci.tugba@gmail.comPurpose: The study aimed to investigate the relationship between self-care management behaviors of individuals with chronic disease and their adaptation to chronic illness.Methods: This cross-sectional and correlational study was conducted with 312 patients treated at a Training and Research Hospital in Turkey between December 2023 and March 2024. The data were collected using a Sociodemographic Characteristics Form, the Self-Care Management Scale in Chronic Illness (SCMP-G) and the Adaptation to Chronic Illness Scale (ACIS).Results: Mean total scores of the participants for SCMP-G were 107.52 ± 12.51 and 77.00 ± 10.00 for ACIS. There was a low-level negative correlation between age and chronic disease adaptation (rh = − 0.201; P < 0.001). Adaptation to chronic illness decreased with increasing age. There was a low-level negative correlation between BMI and physical adaptation (rh = − 0.127; P = 0.026) and self-guarding (rh = − 0.114; P = 0.046). As BMI increased, physical adaptation and self-guarding decreased. Regression analyses revealed that age (β = − 0.115, t = − 0.511, P < 0.05) and economic status (β = 2.698, t = − 2.487, P < 0.05) had a significant effect on adaptation to chronic illness. Multiple regression analysis of the effect of self-guarding and social guarding variables on adaptation to chronic illness was significant (F = 3.504, P < 0.05).Conclusion: Based on the results of the present study, self-care management behaviors have a significant effect on adaptation to chronic illness and individual characteristics affect the results. Individual assistance should be extended to the patients to develop self-care management behaviors, which can induce lifestyle changes and necessary trainings should be planned. Future research should prioritize evaluating nurse-led interdisciplinary interventions and exploring the impact of tailored strategies for specific chronic conditions to improve self-care and adaptation.Keywords: chronic illness, self-care, adaptation, nurses